SEMANTIC MODIFICATIONS OF THE LATEST LOANS IN RUSSIAN MEDIA DISCOURSE (BY THE EXAMPLE OF THE ENGLISH LOANWORD “DOWNSHIFTINGˮ) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-21-30The article examines the structure, morphemic composition and semantics of the English loanword “downshiftingˮ. The research makes a comparative analysis of dictionary definitions in the borrowing language and discovers the integrating semes. The semantic features of the term are further analyzed in Russian media discourse. The study demonstrates a certain semantic discrepancy between the sphere of fixation and communication, revealing a number of semantic modifications in the process of usage. The research concludes that semantic transformations of borrowings are determined by linguistic and extra linguistic factors, allowing for further ambiguous interpretations.Key words: suffixal derivation, interdisciplinary homonym, integrating seme, explicit seme, implicit seme, pejorative semantics, connotation